2011
DOI: 10.1021/jp2074682
|View full text |Cite
|
Sign up to set email alerts
|

On the Atomistic Interactions That Direct Ion Conductivity and Defect Segregation in the Bulk and Surface of Samarium-Doped Ceria: A Genetic Algorithm Study

Abstract: We study the (111) surface of 10.3%, 14.3%, and 18.5% samarium-doped ceria (SDC) using a genetic algorithm (GA) to search for the most energetically stable configurations. In all cases, both Sm ions and oxygen vacancies segregate to the surface, which is similar to experimental findings for 5.3% SDC. 1 Importantly, at the optimal doping level of SDC (∼11%), where conductivity is maximal, defect segregation is limited such that vacancies remain 6 Å apart and pairs of vacancies do not form. At higher concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
(147 reference statements)
2
20
0
Order By: Relevance
“…Here a Sm dopant was located on the top surface, rather than on the subsurface since the Sm dopant tends to segregate on the CeO 2 surface, rather than migrate into the bulk. 25,26 The geometries were optimized until the forces were reduced below 0.05 eV Å À1 . A Hubbard-U term, U = 5 eV, was added to properly describe the localized nature of the 4f electrons of Ce.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Here a Sm dopant was located on the top surface, rather than on the subsurface since the Sm dopant tends to segregate on the CeO 2 surface, rather than migrate into the bulk. 25,26 The geometries were optimized until the forces were reduced below 0.05 eV Å À1 . A Hubbard-U term, U = 5 eV, was added to properly describe the localized nature of the 4f electrons of Ce.…”
Section: Computational Methodologymentioning
confidence: 99%
“…24 A value of 5 eV for the 4f-orbitals of cerium was chosen according to earlier studies. 17,[25][26][27][28][29] In case of the dopants no U-parameter was necessary since the f-electrons were kept frozen in the core. 28,29 The lattice parameter of the unit cell was fixed at 5.49 Å according to our previous calculations.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…17,[25][26][27][28][29] In case of the dopants no U-parameter was necessary since the f-electrons were kept frozen in the core. 28,29 The lattice parameter of the unit cell was fixed at 5.49 Å according to our previous calculations. 17 For Ce ÀCe  Ce distances were shortened in the initial structure by about 0.11 Å and 0.05 Å, respectively.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The same authors also found a maximum in ionic conductivity at approximately 20 atom% for SDC. 3 Although a lot of experimental [4][5][6] as well as theoretical research [7][8][9][10][11][12][13][14][15][16][17][18][19] was conducted in recent years, the exact reason for the maximum remains incompletely explained. One explanation for the decrease in conductivity at high rare earth fractions is the attraction of oxygen vacancies to the trivalent rare earth ions which leads to the trapping of oxygen vacancies and lowered oxygen ion mobility.…”
Section: Introductionmentioning
confidence: 99%